2019
DOI: 10.1002/capr.12255
|View full text |Cite
|
Sign up to set email alerts
|

Early reflections on becoming a therapist: Development of reflective practice in clinical training programmes in an Australian context

Abstract: The development of competent counsellors, psychotherapists and psychologists depends upon not only the clinical competencies, but also the development of the person as the psychotherapist. This qualitative study investigated the experiences of twenty provisional psychologists enrolled in a university-based clinical psychology training programme. Participants were requested to write reflective essays describing their experiences in relation to their first year of training. Utilising an interpretative phenomenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The Council for Accreditation of Counseling and Related Educational Programs requires the incorporation of self‐evaluation and personal reflection in preparing CIT to enter the profession (CACREP, 2016). Through reflective activities such as journaling and expressive arts, students can develop awareness of their values, the evolving counseling relationship, and broader sociocultural and developmental issues (Owens & Neale‐McFall, 2014; Robinson et al., 2019; Villarreal‐Davis et al., 2020). Creative methods for self‐reflection can also serve as a tool for evaluating overall growth when utilized at the end of a training program (Villarreal‐Davis et al., 2020).…”
Section: Counseling Student Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The Council for Accreditation of Counseling and Related Educational Programs requires the incorporation of self‐evaluation and personal reflection in preparing CIT to enter the profession (CACREP, 2016). Through reflective activities such as journaling and expressive arts, students can develop awareness of their values, the evolving counseling relationship, and broader sociocultural and developmental issues (Owens & Neale‐McFall, 2014; Robinson et al., 2019; Villarreal‐Davis et al., 2020). Creative methods for self‐reflection can also serve as a tool for evaluating overall growth when utilized at the end of a training program (Villarreal‐Davis et al., 2020).…”
Section: Counseling Student Developmentmentioning
confidence: 99%
“…Research has shown a notable relationship between self‐efficacy, the belief of one's ability to accomplish a goal (Bandura, 1995), and graduate student development (Moss et al., 2014; Mullen et al., 2015; Robinson et al., 2019). While low self‐efficacy can be part of the learning process, CIT often express increased doubts about their abilities, feelings of insecurity, anxiety, overwhelm, and loneliness (Moss et al., 2014; Pierce, 2016; Robinson et al., 2019), which are important for counselor educators and supervisors to understand. Self‐efficacy can increase as counselors move through their training program, with the greatest incremental growth being between new student orientation and practicum orientation (Mullen et al., 2015).…”
Section: Counseling Student Developmentmentioning
confidence: 99%
“…In the latter, participants, struggling to tolerate 'theoretical tension', underwent 'an ambiguous and anxious process' (p169). Participants of Lowndes and Hanley's study held a different integration approach (Egan's 'Skilled Helper ', 1998) preventing exact comparison to this research project but other studies (Robinson, et al, 2019;Rønnestad, et al, 2019) corroberate a compound picture of vulnerability and uncertainty as a common experience among trainee integrative counsellors (Gold, 2005).…”
Section: Among Psychotherapeutic Approaches Integrationists Are Peculiar In Facing Thismentioning
confidence: 99%
“…As Robinson et al (2019) suggest, the maturity of a therapist is not purely a matter of being clinically competent, it is wholly interrelated with personal development. This study revealed an experience of 'becoming' among participants that has strong resonance with the findings already mentioned in Armitage's study of WIF students (2018).…”
Section: A Sense Of Becomingmentioning
confidence: 99%
See 1 more Smart Citation